2014
DOI: 10.1128/jvi.00208-14
|View full text |Cite
|
Sign up to set email alerts
|

A Complex Comprising Phosphatidylinositol 4-Kinase IIIβ, ACBD3, and Aichi Virus Proteins Enhances Phosphatidylinositol 4-Phosphate Synthesis and Is Critical for Formation of the Viral Replication Complex

Abstract: Phosphatidylinositol 4-kinase III␤ (PI4KB) is a host factor required for the replication of certain picornavirus genomes. We previously showed that nonstructural proteins 2B, 2BC, 2C, 3A, and 3AB of Aichi virus (AiV), a picornavirus, interact with the Golgi protein, acyl-coenzyme A binding domain containing 3 (ACBD3), which interacts with PI4KB. These five viral proteins, ACBD3, PI4KB, and the PI4KB product phosphatidylinositol 4-phosphate (PI4P) colocalize to the AiV RNA replication sites (J. Sasaki et al., E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 48 publications
(79 reference statements)
3
68
0
Order By: Relevance
“…Although, Arf1 and GBF1 seem to be involved in the membrane recruitment and activation of PI4K IIIβ in uninfected cells they are presumed to participate on this process also during the enteroviral infections [90]. Work on Aichi virus led to conclusion that Golgi adaptor protein ACBD3 is the cellular mediator of interaction between 3A protein and PI4K IIIβ [74,104] but details regarding the recruitment of the IIIβ enzyme by enteroviruses are conflicting. siRNA against ACBD3 was reported to both lower and increase the replication of the poliovirus [105,107] but not of the CVB3 or rhinovirus [108,109], which is surprising as the 3A proteins of these enteroviruses are rather similar and their 3A proteins interact with ACBD3 [105].…”
Section: Pi4ks In Health and Diseasementioning
confidence: 95%
See 1 more Smart Citation
“…Although, Arf1 and GBF1 seem to be involved in the membrane recruitment and activation of PI4K IIIβ in uninfected cells they are presumed to participate on this process also during the enteroviral infections [90]. Work on Aichi virus led to conclusion that Golgi adaptor protein ACBD3 is the cellular mediator of interaction between 3A protein and PI4K IIIβ [74,104] but details regarding the recruitment of the IIIβ enzyme by enteroviruses are conflicting. siRNA against ACBD3 was reported to both lower and increase the replication of the poliovirus [105,107] but not of the CVB3 or rhinovirus [108,109], which is surprising as the 3A proteins of these enteroviruses are rather similar and their 3A proteins interact with ACBD3 [105].…”
Section: Pi4ks In Health and Diseasementioning
confidence: 95%
“…The anti-Poliovirus and anti-Coxsackievirus B3 (CVB3) activity of several compounds was linked with their PI4K IIIβ inhibitory activity [102,103]. Sasaki and colleagues showed that this enzyme is also essential in the life cycle of another picornavirus, the Aichi virus (Kobuvirus) and that the virus hijacks PI4K IIIβ through the Golgi residing ACBD3 protein [74,104]. Greninger and colleagues showed that PI4K IIIβ recruitment through the interaction with ACBD3 protein is common to many picornaviruses and suggested that the IIIβ enzyme might be target for a broad anti-picornavirus therapy [105,106].…”
Section: Pi4ks In Health and Diseasementioning
confidence: 98%
“…The underlying mechanism for viral hijacking of PI4KIIIβ is complex and not fully understood. In a subset of enteroviral infections 3A activates the guanine exchange factor Golgi-specific brefeldin A-resistance guanine nucleotide exchange factor 1 (GBF1) for Arf1, leading to activation of PI4KIIIβ [46]. In a number of picornaviruses, including both poliovirus and aichivirus, 3A activation of PI4KIIIβ appears to be mediated by interactions with ACBD3 [43,45,47,48].…”
Section: Pi4kiiiβ-binding Partnersmentioning
confidence: 99%
“…HNF4 ␣ ( 11 ), sterol regulatory element-binding protein (SREBP) 1 ( 12 ), plant AtEBP ( 13 ), and several viral proteins ( 3,(14)(15)(16)(17)(18). Plant ACBP members are also implicated in a multitude of function such as embryogenesis and resistance to various stresses ( 4,5,11 ).…”
mentioning
confidence: 99%